Hubungan antara Demografi Konsumen dengan Kepuasan terhadap Layanan Paket Perawatan Spa di GY Spa Jakartal - Oktadiana, Hera; Yuliana, Yuliana (Bina Nusantara University, 2010)
Spa industry has been growing quite fast in many parts of the world, including Indonesia. The prospect of spa business is still very positive and wide open. There are many varieties of spas offered, such as day spas, hotel-based spas, resort spas and destination spas. Regardless of the type of spa, most spa operators provide massage and nutrition related services. GY Spa, one of the best spa operators in Jakarta offers several spa packages which include body massage, body treatment, body scrub, face massage and aromatheraphy. This research aims to find the correlation between the demographic segmentation and the consumer satisfaction towards the spa packages in GY Spa. Based on the research, it is found that education, occupation and nationality have no correlation toward the consumer satisfaction, while age and gender shown to have correlation. Female and the younger customers are more satisfied with the spa packages offered by GY Spa.Â